Supercritical Carbon Dioxide Extraction of Astaxanthin, Lutein, and Fatty Acids from Haematococcus pluvialis Microalgae - Sanzo, Giuseppe Di (Mar Drugs, 2018)
Haematococcus pluvialis microalgae in the red phase can produce significant amounts of astaxanthin, lutein, and fatty acids (FAs), which are valuable antioxidants in nutraceutics and cosmetics. Extraction of astaxanthin, lutein, and FAs from disrupted biomass of the H. pluvialis red phase using carbon dioxide (CO(2)) in supercritical fluid extraction (SFE) conditions was investigated using a bench-scale reactor in a semi-batch configuration. In particular, the effect of extraction time (20, 40, 60, 80, and 120 min), CO(2) flow rate (3.62 and 14.48 g/min) temperature (50, 65, and 80 °C), and pressure (100, 400, and 550 bar.) was explored. The results show the maximum recovery of astaxanthin and lutein achieved were 98.6% and 52.3%, respectively, at 50 °C and 550 bars, while the maximum recovery of FAs attained was 93.2% at 65 °C and 550 bars.